PENERAPAN ARTIFICIAL INTELLIGENCE (AI) DALAM SISTEM INFORMASI MANAJEMEN PENDIDIKAN ISLAM: TINJAUAN ETIKA DAN EFISIENSI DALAM PERSPEKTIF ISLAM - Nabil Achmad Aufani (STKIP Pesisir Selatan, 2025)
This study aims to analyze the application of Artificial Intelligence (AI) in the Islamic education management information system from an ethical and efficiency perspective based on an Islamic perspective. The advancement of digital technology requires educational institutions to carry out data-based managerial transformations that are fast, accurate, and efficient and able to answer all the demands and needs of society. In this context, Artificial Intelligence plays a role as a solution to support this process. The research method used in this study is Library Research with data collection techniques from literature related to the topic to be discussed in this study, while the data analysis uses the Miles and Huberman style. The results of the study indicate that the use of Artificial Intelligence provides significant benefits to the Management Information System in an educational institution, thus impacting efficiency, professionalism and work results, transparency, and process accountability. However, on the other hand, the use of Artificial Intelligence also poses challenges in the form of algorithmic bias and dehumanization of decisions. Therefore, its implementation must be based on Islamic values which contain the principles of Maqashid As Syari'ah, namely Hifdz Ad Din, Hifdz Al Aql and Maslahah Al Ammah which are then broken down into several sub-principles in the four stages of SIM implementation.